BANJIR DI KOTA BENGKULU: SEBUAH TINJAUAN HISTORIS - Kurniawan, Penadi; Syafrina, Yelda (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research discusses floods in the city of Bengkulu as an initial overview. The cosmology of Bengkulu is closely related to myths about rivers. Rivers are believed to have both negative and positive impacts on human activities, one of which is in the form of flood disasters. Bengkulu is a river-crossing city, which increases the level of flood danger. This study aims to explain the cosmological views of the Bengkulu community regarding the water environment and analyze several factors that have caused sustained floods in Bengkulu from 2008 to the present. This research is a qualitative study using historical methods. Qualitative research produces in-depth descriptive data. The historical research process involves four stages: heuristic (data search and collection), source criticism, interpretation (interpretation of historical facts or evidence), and historiography (historical writing). The data collection techniques used include archival studies and literature reviews. The results of the research show that the Bengkulu community has a number of local wisdom regarding how to maintain harmony with nature and the consequences/warnings of environmental destruction. The research also found that geographical factors in Bengkulu are the main cause of floods, while the utilization of natural resources (coal mining and deforestation) and population growth have resulted in the increasing intensity and impact of periodic floods.